Hyperparasitic Fungi against Melon Powdery Mildew Pathogens: Quantitative Analysis of Conidia Released from Single Colonies of Podosphaera xanthii Parasitised by Ampelomyces - Yutaka Kimura; Márk Z. Németh; Kana Numano; Asami Mitao; Tomomi Shirakawa; Diána Seress; Yoshihiro Takikawa; Koji Kakutani; Yoshinori Matsuda; Levente Kiss; Teruo Nonomura (Agronomy, 2023)
In this study, we evaluated the effectiveness of hyperparasitic fungi in controlling powdery mildew (PM). In a greenhouse, we spray-inoculated single colonies of the melon PM-causing fungus Podosphaera xanthii strain KMP-6N at three different fungal developmental stages (i.e., 5, 10, and 15 days old) with spores of the hyperparasitic fungus Ampelomyces sp. strain Xs-q. After spray inoculation, we collected and counted KMP-6N conidia produced as asexual progeny from PM colonies using an electrostatic rotational spore collector. Collector insulator films were replaced at 24 h intervals until KMP-6N ceased to release additional progeny conidia. Conidial releases from each of the single Xs-q-inoculated KMP-6N colonies gradually reduced, then stopped within ca. 4 and 8 days of the first treatment in 5- and 10-day-old KMP-6N colonies, and within ca. 20 days of the second spray treatment in 15-day-old KMP-6N colonies, respectively. The total numbers of asexual progeny conidia collected from single 5-, 10-, and 15-day-old colonies were ca. 156, 1167, and 44,866, respectively. After electrostatic spore collection, conidiophores in Xs-q-uninoculated KMP-6N colonies appeared normal, whereas almost all conidiophores in 5- and 10-day-old Xs-q-inoculated KMP-6N colonies were completely deformed or collapsed due to the infection of the hyperparasitic fungus. This is the first study to apply electrostatic and digital microscopic techniques to clarify the impact of fungal hyperparasitism on mycohost survival, and, in particular, to assess quantitatively and visually the suppression of conidial release from any PM colonies infected with Ampelomyces.